Advanced epithelioid hemangioendothelioma of the liver: could lenvatinib offer a bridge treatment to liver transplantation?. (March 2022) - Kounis, Ilias; Lewin, Maïté; Laurent-Bellue, Astrid; Poli, Edoardo; Coilly, Audrey; Duclos-Vallée, Jean-Charles; Guettier, Catherine; Adam, René; Lerut, Jan; Samuel, Didier; Rosmorduc, Olivier
In this article, we describe the case of a 34-year-old woman presenting a multifocal and metastatic epithelioid hemangioendothelioma (HEHE) of the liver. Under classical chemotherapy using cyclophosphamide, there was a fast tumor progression in liver and extra-hepatic metastatic sites (lungs and mediastinal lymph node). Taking into account the patient's age and the natural history of the HEHE, our goal was to try to bring her to liver transplantation (LT) and lenvatinib was an acceptable candidate for this reason. Shortly after the initiation of lenvatinib before LT and surgery, we observed the enlargement of large devascularized necrotic areas in most of the liver HEHE masses, suggesting a good response. The patient was finally transplanted 6 months after initiation of lenvatinib treatment. Eight months after LT, progression occurred (ascites, peritoneal recurrence, and mediastinal lymph node). After restarting lenvatinib, ascites disappeared and the lymph node decreased in size, suggesting a good response, more than 1 year after her transplantation. This is the first case report to our knowledge that illustrates the benefit of lenvatinib as a neoadjuvant bridge until LT for a multifocal and metastatic HEHE. In addition, this drug has also shown a benefit in term of disease control after a late recurrence of the tumor. We suggest that lenvatinib should be proposed as a bridge to the LT for nonresectable HEHE. Moreover, this drug was also beneficial in the treatment of late recurrence after LT. The absence of pharmacologic interactions between classical immunosuppressive drugs and lenvatinib may allow its use as an early adjuvant approach when the risk of recurrence is high. The strength of our case consists in the long follow-up and the innovative message allowing changing palliative strategies into curative ones in case of advanced HEHE.